Assessing Confidence in Antidepressant Prescribing Amongst the Foundation Year Cohort - Abigail Spiteri; Gareth Smith (BJPsych Open, 2025)
Aims: The aim of this quality improvement project was to assess, and improve the confidence in antidepressant prescribing and management of common side effects amongst the Foundation Year (FY) trainees.